2016
DOI: 10.1177/1474704916631614
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Perception of Physical Attractiveness

Abstract: Waist-to-hip ratio (WHR) and breast size are morphological traits that are associated with female attractiveness. Previous studies using line drawings of women have shown that men across cultures rate low WHRs (0.6 and 0.7) as most attractive. In this study, we used additional viewing measurements (i.e., first fixation duration and visual regressions) to measure visual attention and record how long participants first focused on the female body and whether they regressed back to an area of interest. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 36 publications
4
30
2
3
Order By: Relevance
“… 12 In contrast, others have shown that men fixate proportionately less on the face than on the body when the images are sexualized or nude. 11 , 13 , 14 Although it might be expected that AD-treated men would look less at the pelvis and breasts compared with men in the 2 non-AD groups (ie, no-AD and HC), we did not observe group differences for preferential viewing of specific AOIs. One possible explanation for these discrepancies is that the stimuli used in our study represented material that was especially novel for our elderly participants, causing them overall to focus more on sexually relevant areas (ie, chest, pelvis) rather than other areas, such as faces.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“… 12 In contrast, others have shown that men fixate proportionately less on the face than on the body when the images are sexualized or nude. 11 , 13 , 14 Although it might be expected that AD-treated men would look less at the pelvis and breasts compared with men in the 2 non-AD groups (ie, no-AD and HC), we did not observe group differences for preferential viewing of specific AOIs. One possible explanation for these discrepancies is that the stimuli used in our study represented material that was especially novel for our elderly participants, causing them overall to focus more on sexually relevant areas (ie, chest, pelvis) rather than other areas, such as faces.…”
Section: Discussioncontrasting
confidence: 61%
“… 9 , 11 , 12 In addition, compared with women, men tend to focus their attention on regions of the female body that signal health and fertility, such as the face, breasts, and midriff. 12 , 13 , 14 Fixation on these areas also correlates with sexual interest as measured by changes in pupil diameter 12 and penile plethysmographic data. 15 …”
Section: Introductionmentioning
confidence: 97%
“…Numerous eye-tracking studies have provided empirical evidence that the breasts and hips (as part of the WHR) of women are important visual sources of information (Dixson et al, 2011; Garza et al, 2016). However, various eye-tracking studies have also underlined that the visual importance of the body regions is linked to the task on which the participants are focusing and the explicitness of the stimuli.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The implicit measurement of eye tracking enables unbiased insights into the visual attention toward women and sexualized robots, as it is not influenced by social desirability, which is particularly important given that the theme of sex robots might lead to biased reactions. Garza et al (2016), who themselves conducted an eye-tracking study on the perception of the female body, highlight why eye tracking is useful in this research area by stating that “Eye movements provide a ‘true’ measure because they reflect ongoing mental processes in real time, whereas ratings are typically ‘ post hoc’ processes that rely more on problem solving strategies” (p. 14). Moreover, we are interested in whether the robots’ appearance, in terms of how human-like or machine-like they look, influences gaze patterns.…”
Section: Introductionmentioning
confidence: 99%
“…8 1 Maner et al 2007Duncan et al 2007Duncan et al 2007Garza, Heredia, & Cieslicka, 2016 Duncan et al 2007Duncan et al 1990Rose & Frieze, 1993Buss & Schmitt, 1993Buss & Schmitt, 19931990;Rose & Frieze, 19932016 2…”
mentioning
confidence: 99%